Healthcare professionals discourses on men and masculinities in sexual healthcare: a focus group study - Tommy Persson; Jesper Löve; Ellinor Tengelin; Gunnel Hensing (BMC, 2023)
Abstract Studies have reported that men's uptake of sexual health services is low, that these services make them feel vulnerable, and that they experience sexual healthcare (SHC) as stressful, heteronormative, potentially sexualised and "tailored for women". They also suggest that healthcare professionals (HCPs) working in SHC view masculinity as problematic, and situated in private relationships. This study aimed to explore how HCPs construct the gendered social location in SHC, specifically in terms of masculinity and a perception that masculinity is situated in relationships. Critical Discourse Analysis was used to analyse transcripts from seven focus group interviews with 35 HCPs working with men's sexual health in Sweden. The study found that gendered social locations were discursively constructed in four ways: (I) by problematising and opposing masculinity in society; (II) through discursive strategies where a professional discourse on men and masculinity is lacking; (III) by constructing SHC as a feminine arena where masculinity is a visible norm violation; (IV) by constructing men as reluctant patients and formulating a mission to change masculinity. The discourses of HCPs constructed the gendered social location of masculinity in society as incompatible with SHC, and saw masculinity in SHC as a violation of feminine norms. Men seeking SHC were constructed as reluctant patients, and HCPs were seen as agents of change with a mission to transform masculinity. The discourses of HCPs risk othering men in SHC, which could prevent care on equal terms. A shared professional discourse on masculinity could create a common foundation for a more consistent, knowledge-based approach to masculinity and men's sexual health in SHC.